Investigation of Genetic Relatedness of Brucella Strains in Countries Along the Silk Road - Liu, Zhiguo; Wang, Chengling; Wei, Kongjiao; Zhao, Zhongzhi; Wang, Miao; Li, Dan; Wang, Heng; Wei, Qiang; Li, Zhenjun (Frontiers in Veterinary Science, 2021)
This study was conducted to investigate the genetic Relatedness of Brucella strains in countries along the silk road and provide information for the prevention of cross-border transmission of brucellosis. Multiple locus variable-number tandem repeat analysis (MLVA) data of Brucella strains were downloaded from the international MLVAbank database and then further standardized using the Excel 2016 software, after which the BioNumerics 7.6 software was applied to the constructed Minimum Spanning Tree (MST) to explore the geographic origins and genetic relationships of strains analyzed. A total of 1386 Brucella strains were analyzed in this study: 413 B. abortus strains (29.8%), 911 B. melitensis strains (65.7%) and 62 B. suis strains (4.5%). B. melitensis biovar 3 was the dominant species in the examined regions. Wide host lineages were observed among this population, including a variety of livestock and wildlife. B. abortus strains from the examined regions had common geographic origins and evolutionary ancestors. In addition, the epidemic range of B. abortus strains was limited, with the majority spreading within the national borders. Extensive gene-shared events were observed among B. melitensis populations from the same geographic origin, suggesting that B. melitensis brucellosis originate from multiple common sources of infection. B. suis strains from different nations that showed unique geographic origins and evolution profiles had no significant epidemiological correlation observed among strains. Control of transfer and trade in infected sheep are great challenges in countries along the silk road; therefore, scientific research cooperation should be strengthened to improve the diagnosis of animal brucellosis. With the rising interest of the scientific community in brucellosis, a broad-spectrum vaccine against Brucella is expected.